Antibiotic Disruption of the Gut Microbiota Enhances the Murine Hepatic Dysfunction Associated With a High-Salt Diet - Zhang, Zheng; Li, Mengjie; Cui, Bo; Chen, Xiao (Frontiers in Pharmacology, 2022)
Epidemiological and experimental evidence indicates that antibiotic exposure is related to metabolic malfunctions, such as obesity and non-alcoholic fatty liver disease (NAFLD). Liver impairment and hypertrophy of adipose cells are related to high salt consumption. In this research, a high salt diet (HSD) enhanced antibiotic-induced hepatic injury and mitochondrial abnormalities in mice. The physiological mechanism of NAFLD in the intestine was evaluated. The mice were fed a HSD with or without penicillin G (PEN) for eight weeks and the gut metabolome, untargeted faecal metabolomics, and intestinal function were evaluated. The results revealed that HSD, PEN and their combination (HSPEN) significantly changed the gut microbial community. HSPEN mice exhibited more opportunistic pathogens (such as Klebsiella and Morganella) and reduced probiotic species (including Bifidobacterium and Lactobacillus). The main variations in the faecal metabolites of the HSPEN group were identified, including those connected with entero-hepatic circulation (including bile acids), tryptophan metabolism (i.e., indole derivatives) and lipid metabolism (e.g., erucic acid). Furthermore, increased intestinal permeability and immunologic response caused greater hepatic damage in the HSPEN group compared to the other groups. Thus, antibiotic exposure with HSD consumption is conducive to NAFLD development and progression. These findings may have important implications for public health.